The issue of metaphor and transcendence in the attributes of God on Ibn Taymiyyah | قضية التشبيه والتنزيه في صفات الله الخبرية عند ابن تيمية - Zul Ashfi (Al-Zahra : Journal for Islamic and Arabic Studies, 2010)
The topic of the research is about theology; in case of tasybih and tanzih relatedto the attributes of God according to i:he lbn Taimiyah view. TI1is studyconcludes that Ibn Taimiyah was inconsistent in understanding the texts of alQuranand Hadith related to tasybih (jihah, wajh, istiwa '). In case of Jihah (Allahhas a place)., Ibn Taimiyah dissent with the views of the majority, he did notreco~~ jzhah and <legates it. But in other case of tasybih, he used the methodof taJwidh (submit; he submit this case to Allah), while accused to those who usethis method as Ahl bid'ah. Feature of the research is the original study in theview of Ibn Tayrniyyah, especially in case of tasybih. This study used classicalreferences and Ibn Taimiyan books.